2020
DOI: 10.3390/nu12051528
|View full text |Cite
|
Sign up to set email alerts
|

Meat Consumption, Cognitive Function and Disorders: A Systematic Review with Narrative Synthesis and Meta-Analysis

Abstract: Cognitive impairment, Alzheimer’s disease, and other forms of dementia are increasing in prevalence worldwide, while global dietary patterns are transitioning to a ‘western type’ with increasing meat consumption. Studies which have explored the associations between cognitive function and meat intakes have produced inconsistent findings. The aim of this systematic review was to explore the evidence linking meat intake with cognitive disorders. Twenty-nine studies were retrieved, including twelve cohort, three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
2
27
1
Order By: Relevance
“…Consistent with the results from previous reviews 7 , 22 , in the adjusted model, we showed the benefits of habitual consumption of fish and unprocessed red meat on general cognitive ability. As fish contains some essential macronutrients including protein and unsaturated fatty acids 23 and as unprocessed red meat is a good source of protein, and B group vitamins 24 , our findings could be explained by the positive associations observed with cognition and (i) B vitamins, (ii) n−3 fatty acids, (iii) proteins, and (iv) dietary patterns that are moderately high in protein (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results from previous reviews 7 , 22 , in the adjusted model, we showed the benefits of habitual consumption of fish and unprocessed red meat on general cognitive ability. As fish contains some essential macronutrients including protein and unsaturated fatty acids 23 and as unprocessed red meat is a good source of protein, and B group vitamins 24 , our findings could be explained by the positive associations observed with cognition and (i) B vitamins, (ii) n−3 fatty acids, (iii) proteins, and (iv) dietary patterns that are moderately high in protein (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…For other food items, meat consumption was generally considered to have an adverse effect on cognitive outcomes due to its high saturated fat content [ 47 , 48 ] which is potentially associated with the overproduction of circulating free fatty acids and systemic inflammation. However, the specific effect of meat consumption on cognitive disorders was often discordant [ 18 ]. A longitudinal study of a large cohort with a mean follow-up of 9.8 years and active ascertainment of dementia showed that low meat consumption (≤1 time/week) was associated with an increased risk of cognitive impairment compared with regular consumption (≥4 times/week) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased consumption of fish or nuts was observed to reduce the risk of MCI [ 7 , 15 , 16 ], benefiting cognitive abilities. Few studies have examined the effect of staple foods [ 17 ] or meat [ 18 ] that are generally considered to have negative effects on health because of their high contents of carbohydrate or saturated fat. Most previous studies, however, tended to focus on the outcome of MCI, without data specifically on subtypes of MCI, including single domain/multidomain amnestic and non-amnestic subtypes [ 19 ], which feature as deficits of distinct cognitive domains related to unequal brain function and have varied prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low meat consumers also ate less fish, fruit and vegetables, therefore, they could have low dietary intake in general and some nutritional deficiencies (31). No strong association between meat consumption and cognitive decline was observed in the meta-analysis by Zhang et al (32).…”
Section: Food Groupmentioning
confidence: 95%